Efficacy of autologous serum as an adjunct treatment for A melting corneal ulcer in A captive Asian elephant - Thittaya Janyamethakul (2018)
This is the first case report on the use of autologous serum as an adjunct to successfully treat a melting corneal ulcer in a captive Asian elephant (Elephas maximus). A 40-year-old female Asian elephant was presented with epiphora of the right eye. It had already received treatment for 3 weeks, but had not responded to conventional treatment with antibiotics and analgesic eye drops. Upon examination, a melting corneal ulcer was found. The elephant received a combined treatment that included autologous serum twice a day for 79 days in addition to antibiotic, antifungal and analgesic drugs administered topically. After just 19 days of treatment, neovascularization of the ulcer site occurred and the ulcer reduced in size, which indicated that the elephant responded well to the treatment. The autologous serum, antibiotic and antifungal eye drops were continued for an additional 2 months to prevent secondary infection during the corneal healing. Throughout the treatment, the elephant lived and worked as usual. This study demonstrated the benefits of using autologous serum as a combined treatment for a melting corneal ulcer in a captive Asian elephant. Autologous serum has tear properties to bathe the eye and is also rich in growth factors and anti-collagenase, which can promote wound healing.